The effect of rotational speed and dwell time on Al/SiC/Cu composite made by friction stir spot welding - Bagheri, Behrouz; Alizadeh, Mehdi; Mirsalehi, Seyyed Ehsan; Shamsipur, Ali; Abdollahzadeh, Amin (Welding in the world, 2022)
Friction stir spot welding (FSSW) was implemented to joining of AA2024-T4 and commercially pure copper with SiC nanoparticles as a reinforcing particle with different rotational speeds (1300, 1600, and 1900 rpm) and dwell times (2, 4, and 6 s). For this purpose, macro- and microstructures, shear tensile strength, and microhardness of joints were investigated. The grain size of the stir zone on the Cu and Al sides decreased from 45.1 to 10.5 μm and 62.2 to 14.5 μm, respectively, as rotational speed and dwell time decreased. The size of the weld zone increased as rotational speed and the dwell time increased. The main reason behind this phenomenon was discussed with the help of geometric parameters and generated heat with respect to different joining conditions. The XRD and the EDS analysis also revealed the formation of AlCu and Al 2 Cu intermetallic compounds (IMCs) in the weld zone, while the thickness of the IMCs layer in the interface joint increased as heat input increased. There is a direct relationship between the shear strength of weld samples and rotational speed and the dwell time during the FSSW process because of the applied optimal welding parameters. The microhardness was significantly improved from HV 122 to HV 156 with an increase in rotational speed and dwell time due to the formation of the IMCs layer, the pinning effect, and the Cu fragment in the stir zone. The fracture surface analysis showed the ductile fracture for all weld samples joined under optimal welding conditions.